2016
DOI: 10.3390/medicines3010008
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Crosslinked Chitosan Hydrogels for the Controlled Release of Antimicrobial Essential Oils and Metal Ions for Wound Management Applications

Abstract: The emerging problems posed by antibiotic resistance complicate the treatment regime required for wound infections and are driving the need to develop more effective methods of wound management. There is growing interest in the use of alternative, broad spectrum, pre-antibiotic antimicrobial agents such as essential oils (e.g., tea tree oil, TTO) and metal ions (e.g., silver, Ag+). Both TTO and Ag+ have broad spectrum antimicrobial activity and act on multiple target sites, hence reducing the likelihood of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The reports have shown that the addition of essential oils to a matrix contributes toward reducing the required doses of the essential oils, while retaining their antioxidant-antimicrobial activity [ 32 ]. We hypothesized that the synergistic effects between essential oils and CBM/CMC enhanced the overall antimicrobial activity against E. coli and S. aureus , as the network structure of the CBM/CMC hydrogel delays the release of essential oils [ 33 ]. Plant essential oils, produced by plants as secondary metabolites, have been reported to possess effective bioactivity and biocompatibility owing to constituents such as terpenoids, phenolics and polyphenols [ 9 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reports have shown that the addition of essential oils to a matrix contributes toward reducing the required doses of the essential oils, while retaining their antioxidant-antimicrobial activity [ 32 ]. We hypothesized that the synergistic effects between essential oils and CBM/CMC enhanced the overall antimicrobial activity against E. coli and S. aureus , as the network structure of the CBM/CMC hydrogel delays the release of essential oils [ 33 ]. Plant essential oils, produced by plants as secondary metabolites, have been reported to possess effective bioactivity and biocompatibility owing to constituents such as terpenoids, phenolics and polyphenols [ 9 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, diffusion and drug release are affected by different parameters such as the hydrophilicity/hydrophobicity of the drug, the surface area and geometry of the hydrogel, the type and volume of solvent, the degradation of the hydrogel, the mesh size and the swelling rate [36]. Different volumes, solvents, ratios of hydrogel to solvent, flasks (e.g., universal, conical flasks), the presence of dialysis membranes and different shaking rate were found to be variable in a review of the literature [23,[37][38][39][40]. In the current study, the drug release was evaluated over 48 h, the amount of compounds released were a function of the initial content of oil.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the difficulties in maintaining homogeneity, ionically crosslinked hydrogels have demonstrated preliminary success when utilized as therapeutic depots, both for the treatment of antibiotic resistant biofilms 73 and the rapid regeneration or revascularization of damaged tissues 74 . Notably, Schmitt et al demonstrated that ionically crosslinked hybrid alginate/0.1% PEG/0.1% HA gels could be used as injectable carriers for the delivery of autologous mesenchymal stem cells (MSCs) into wound sites post injury 75 .…”
Section: Non-covalent Hydrogelsmentioning
confidence: 99%